International dividend policy: legal influence, firm attributes and the desire to pay. - Ho, Pei Yui. (2008)
Recent studies, like Fama and French (2001), provide evidence that the number of dividend payers in the US. has been declining over the past few decades. They attributed these changes to the changing characteristics of the firms as well as a declining propensity to pay dividends. This thesis seeks to determine whether the documented decline in number of dividend payers is purely a U.S. phenomenon or represents a trend in global corporate payout policy.